2021
DOI: 10.1093/hmg/ddab349
|View full text |Cite
|
Sign up to set email alerts
|

WNT11, a new gene associated with early onset osteoporosis, is required for osteoblastogenesis

Abstract: Monogenic early-onset osteoporosis (EOOP) is a rare disease defined by low bone mineral density (BMD) that results in increased risk of fracture in children and young adults. Although several causative genes have been identified, some of the EOOP causation remains unresolved. Whole-exome sequencing revealed a de novo heterozygous loss-of-function mutation in WNT11 (NM_004626.2:c.677_678dup p.Leu227Glyfs*22) in a 4-year-old boy with low BMD and fractures. We identified two heterozygous WNT11 missense variants (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 60 publications
(48 reference statements)
0
8
0
Order By: Relevance
“…Interestingly, we have recently shown that the heterozygous loss-of-function mutation of WNT11 in humans exhibits the opposite phenotype. 53 In a model of a WNT11 heterozygous mutant human osteoblast-like cell line generated by CRISPR-Cas9, we showed that the noncanonical pathway acts upstream of the canonical pathway, since in the absence of WNT11 , the canonical pathway could not be rescued 53 as was also observed in wnt11f2 tx226 mutant zebrafish. 5 This finding combined with our finding of HBM in wnt11f2 heterozygous zebrafish suggests that the noncanonical Wnt pathway is key to bone differentiation independent of bone patterning.…”
Section: Concluding Remarks and Perspectivesmentioning
confidence: 73%
“…Interestingly, we have recently shown that the heterozygous loss-of-function mutation of WNT11 in humans exhibits the opposite phenotype. 53 In a model of a WNT11 heterozygous mutant human osteoblast-like cell line generated by CRISPR-Cas9, we showed that the noncanonical pathway acts upstream of the canonical pathway, since in the absence of WNT11 , the canonical pathway could not be rescued 53 as was also observed in wnt11f2 tx226 mutant zebrafish. 5 This finding combined with our finding of HBM in wnt11f2 heterozygous zebrafish suggests that the noncanonical Wnt pathway is key to bone differentiation independent of bone patterning.…”
Section: Concluding Remarks and Perspectivesmentioning
confidence: 73%
“…Wnt11 has an important promoting effect on cardiac tissue proliferation and tumor cell proliferation [ 15 19 ]. Given the similarity between synovial hyperplasia and angiogenesis in RA and cardiac tissue hyperplasia and tumor pathology, we investigated the expression changes and roles of Wnt11 in RA.…”
Section: Resultsmentioning
confidence: 99%
“…Wnt11 is one of the extracellular Wnt proteins involved in the Wnt signaling pathway. Wnt11 can activate the Wnt signaling by inducing the recombinant RSPO2/leucine-rich repeat containing G protein-coupled receptor 5 (LGR5) complex through the noncanonical Wnt pathway [ 15 ]. Wnt11 also promotes angiogenesis by activating the atypical Wnt11/PKC/JNK signaling pathway [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Interference with WNT11 led to inhibition of axial elongation of the embryo on the anterior and posterior axes [ 43 ]. WNT11 is also involved in the development of the skeletal system and contributes to bone homeostasis during osteogenic differentiation [ 44 ]. Alternatively, MSRB3 , HMGA2 , and PTCH1 have plausible biological functions associated with body size.…”
Section: Discussionmentioning
confidence: 99%